Improving Speaking and Communication Ability Using Puppet Stage Media in Preschool - Anisa, Ika Silvi; Hartati, Sulis Janu (Pusat Penerbitan Universitas (P2U) Unisba, 2024)
This research aims tspaceermine the effectiveness of using learning media in the form of puppet stage media to improve speaking and communication skills in playgroup children. In general, the use of puppet stage media is used to improve children's language skills, but in this research, it is used as an effort to improve speaking and communication skills in students, especially playgroup children. This research is a quantitative research using observation methods. The subjects of this research were play group students with a total of 12 children. The results of the research show that there is an increase in students' speaking and communication skills after using puppet stage media. To determine the results of this research, researchers used a non-parametric test (Wilcoxon Test) with a pretest average of 7.08 and a posttest average of 18.17. The results of the analysis in this research are that there is an increase in speaking and communication skills after using puppet stage media in playgroup students.